Multiidentidades culturais: uma análise da construção das multiidentidades culturais nas sociedades pós-modernas, tendo como referência o vídeo FROM, uma pesquisa visual da cidade de Londres - Gomes, Elisa Marsiaj (2008)
The objective of this approach is to investigate the cultural multiidentities construction process in post-modern societies by analysis of the video FROM a visual research of the city of London and, consequently, also to reflect about the production of knowledge by visual thought way. Methodologically, the concepts of ryzom and multiplicity by Deleuze and Guattari were fundamental, as were the theoreticians, Manuel Castells, Massimo Canevacci, Nestor Canclini and Stuart Hall, for the comprehension of the relation network in these societies. In order to consider the visual production in the scientific research development, the notion of relation thinking, by André Parente, and the studies of hipermidiatic environment, by Sérgio Bairon, were utilized. In the first stage, based on FROM, this investigation relates the concept of ryzom with the mesh which permeates cosmopolitan cities, identifies the multiple cultural identities and analyses how they are constructed and deconstructed in this network of connections and fluxes, upon which the construction process of visual research is analyzed as a thought by images and in network. Besides the text, a hypermedia was created, showing relations established during the whole work process. This is the visual and interactive result of an artistic-scientific interdisciplinary research which allows for production of knowledge